Perancangan Sistem Informasi Bimbingan Skripsi Online (SIBIMO) dengan SCRUM Framework - Roji, Fikri Fahru; Shiddieq, Diqy Fakhrun; Gusdiana, Ridian; Puspita, Evi (Institut Teknologi Garut, 2023)
The development of technology and the internet has opened up opportunities for advances in information systems. In this context, the Online Thesis Guidance Information System (SIBIMO) is an efficient solution in the thesis guidance process in higher education. With the SCRUM method, SIBIMO allows students to submit thesis titles, interact with supervisors, and manage seminar and trial stages through a designed user interface. This methodology combines stages such as UI design, functionality testing, and progress evaluation. Testing each SIBIMO menu ensures the system is running as intended. SCRUM allows achieving development time targets and efficient adaptation at each iteration. This research concludes that SIBIMO, which was developed using the SCRUM method, was successful in designing an Information System that was carried out effectively and efficiently in managing the Online Tutoring Information System design process.